2014
DOI: 10.1002/jsfa.6797
|View full text |Cite
|
Sign up to set email alerts
|

Water scarcity conditions affect peach fruit size and polyphenol contents more severely than other fruit quality traits

Abstract: The increase in stress intensity strongly affected fruit mass. The concentration of total carbohydrates and organic acid at harvest increased mainly through a decrease in fruit dilution, whereas the concentrations of polyphenols were also strongly affected through an impact on their metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 40 publications
6
30
2
2
Order By: Relevance
“…The expression of specific genes responsible for anthocyanin synthesis has been shown to increase during water deficits . Rahmati et al obtained similar results in their research on peach grown under DI, and Tovar et al detected an increase in phenylalanine ammonia lyase in drought‐affected olives. Total flavanol content generally increased under DI in cv.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The expression of specific genes responsible for anthocyanin synthesis has been shown to increase during water deficits . Rahmati et al obtained similar results in their research on peach grown under DI, and Tovar et al detected an increase in phenylalanine ammonia lyase in drought‐affected olives. Total flavanol content generally increased under DI in cv.…”
Section: Discussionmentioning
confidence: 78%
“…The earliest visible response of strawberry plants to water deficit is the inhibition of growth and reduced productivity . In addition, physiological response to water stress can be expressed in a series of morphological changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 The detection of higher levels of cyanidin 3-glucoside and cinnamic acids as compared to other compounds, especially chlorogenic acid, are consistent with results early reported in other peach cultivars. 40,41,54…”
Section: Discussionmentioning
confidence: 99%
“…'White River' was larger than previously reported, with a 10-to 14-year fruit weight of 201 g (Clark and Moore, 2003). A study by Rahmati et al (2015) indicated that when drought stress is high, fruit weight is negatively affected. The 2017 harvest was an exceptionally wet year in Arkansas, with 455 mm of rain from April to June, which could have contributed to the increased fruit weight.…”
Section: Physicochemical Attributes At Harvestmentioning
confidence: 75%